Empirical Study on the Determinants of Unemployment Rate in Algeria - Amel, Chadlia (The journal of contemporary issues in business and government, 2023)
The purpose of this empirical study is to analyze the impact of specific variables on Algeria’s unemployment rate between 1995 and 2021. To achieve this, we utilized the Vector Auto Regressive (VAR) model. The variables considered in our analysis encompass the unemployment rate, economic growth rate, entrepreneurial activity, Human Development Index, and the number of internet users. This paper is structured into two principal sections. The first section provides a literature review concerning the factors influencing the unemployment rate. In the second section, we present our empiricalstudy to establish the relationship between the unemployment rate andthe other variables. The main results of this study demonstrate that economic growth rate, entrepreneurial activity, and the Human Development Index contributeto a reduction in Algeria’s unemployment rate. However, the variable related to internet usage intensity was not included in the final equationof the VAR3 model. Even in Granger causality tests, its impact was found to be statistically insignificant.